An Analysis of The Metaphor’s Meanings in The Original Soundtrack of One Piece - Darmawan, Putu Mas (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to verify the types of metaphor and to find metaphor's meaning of original soundtrack of One Piece's lyrics. The method of this study are listening and documentation. This study was analyzed by descriptive qualitative which the main instrument is card data. The lyrics of this article seen as poem. The types of metaphor and metaphor's meaning were analyzed using the theory of metaphor by Knowless and Moon (2006). The finding shows that were 28 data using metaphor, there were 5 personification, 10 simile, 10 metonymy, and 3 synthetic. The using metaphors on lyrics of One Piece are to represent spirits, friendship, and obstacles of the adventure to fulfill our dreams .